Policy Networks in Handling Covid-19 in Lhokseumawe-Indonesia - Rauza Utari; Aiyub Aiyub; Nurhafni Nurhafni; Muryali Muryali; Maryam Maryam (Master Program of Sociology, Universitas Malikussaleh,, 2021)
This study examined the dimensions of the policy networks in handling Covid-19. This research used a qualitative approach with data collection techniques through interviews, observation and documentation. While data analysis techniques used was an interactive analysis model. The results showed that: 1). the composition of the policy network for handling COVID-19 is still dominated by government elements; 2) the function of the policy network in the context of communication has been established between actors but miscommunication is still found in dealing with Covid-19. 3) The level of network institutionalization in the policy for handling Covid-19 is high 4) there are still inconsistencies in the activities of handling Covid-19 in the field, and 5) The private sector plays an active role in supporting facilities and needs in the network for handling COVID-19.